Effect of telemonitoring of cardiac implantable electronic devices on healthcare utilization: a meta‐analysis of randomized controlled trials in patients with heart failure. (27th January 2016) - Klersy, Catherine; Boriani, Giuseppe; De Silvestri, Annalisa; Mairesse, Georges H.; Braunschweig, Frieder; Scotti, Valeria; Balduini, Anna; Cowie, Martin R.; Leyva, Francisco; ,
Abstract : Aims: Implantable device telemonitoring (DTM) is a diagnostic adjunct to traditional face‐to‐face hospital visits. Remote device follow‐up and earlier diagnoses facilitated by DTM should reduce healthcare utilization. We explored whether DTM reduces healthcare utilization over standard of care (SoC), without compromising patient outcomes. Methods and results: This systematic review and meta‐analysis of 11 randomized controlled trials on DTM in patients with heart failure consisted of 5702 patients, with a median of 117 [interquartile range (IQR) 76–331] patients per study [age 65 years (IQR 63–67)] and follow‐up range of 12–36 months. DTM was associated with a reduction in total number of visits [planned, unplanned, and emergency room (ER)] [relative risk (RR) 0.56; 95% confidence interval (CI) 0.43–0.73, P < 0.001]. Rates of cardiac hospitalizations (RR 0.96; 95% CI 0.82–1.12, P = 0.60) and the composite endpoints of ER, unplanned hospital visits, or hospitalizations (RR 0.99; 95% CI 0.68–1.43, P = 0.96) was similar between the DTM and the SoC groups. An increase in the total number of ER or unscheduled visits (RR 1.37; 95% CI 1.11–1.70, P = 0.004) was observed. This effect was consistent and statistically significant for all studies. Total and cardiac mortality were similar between the groups (DTM RR 0.90; 95% CI 0.69–1.16, P = 0.41; and DTM RR 0.93; 95% CI 0.51–1.69, P = 0.80). Monetary costs favoured DTM (10–55% reduction in five studies). Conclusions: Compared with SoC, DTM is associated with a marked reduction in planned hospital visits. In addition, DTM was associated with lower monetary costs, despite a modest increase in unplanned hospital and ER visits. DTM did not compromise survival.